2018
DOI: 10.1002/2017gc007239
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Composition of Arctica islandica Aragonite in the Context of Shell Architectural Organization: Implications for Paleoclimate Reconstructions

Abstract: The analysis of the stable isotopic composition of bivalve shells provides the data needed to construct climate records at high temporal resolution. Yet, the reproducibility of the results and the effect of microstructural organization on the isotopic signature and measurements have not been extensively studied. Here, we examine the architectural changes within Arctica islandica shells, specifically if samples from microstructurally different shell layers differ in respect to stable oxygen isotope values. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…In other bivalve taxa, different biomineralization processes between the outer crossed‐lamellar and inner prismatic shell layers may cause different isotopic fractionation. Trofimova et al (2018) found lower δ 18 O values in the outermost homogenous prismatic/granular portion of the outer shell layer of Arctica islandica relative to the crossed‐acicular/lamellar inner portion of the outer layer. This opposes the pattern in Tridacna , which have lower δ 18 O values in their crossed‐lamellar shell layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In other bivalve taxa, different biomineralization processes between the outer crossed‐lamellar and inner prismatic shell layers may cause different isotopic fractionation. Trofimova et al (2018) found lower δ 18 O values in the outermost homogenous prismatic/granular portion of the outer shell layer of Arctica islandica relative to the crossed‐acicular/lamellar inner portion of the outer layer. This opposes the pattern in Tridacna , which have lower δ 18 O values in their crossed‐lamellar shell layer.…”
Section: Discussionmentioning
confidence: 99%
“…The lower oxygen isotope ratios recorded in the outer shell layer versus the inner layer suggests attention should be paid to the shell regions used when comparing the results of separate reconstructions. Additional investigations of intrashell oxygen isotope variability will be needed for other bivalve taxa, which are paleoclimate proxy targets (Cusack et al, 2016; Trofimova et al, 2018). We also found that shell carbon isotope ratios did not conform with known variations in photosymbiotic activity between closely related giant clam species, suggesting that different proxies should be prioritized in future efforts to identify photosymbiosis in fossil bivalves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the homogeneous microstructure (HOM) in the outer portion of the outer shell layer of A. islandica gradually merges into crossed-acicular (CA) microstructure toward the myostracum (Fig 1A-1D) [27,28]. In addition, the thickness of the HOM portion increases with ontogenetic age [29]. Yet, fine complex crossed-lamellar (FCCL) microstructure occurs in the inner portion of the outer shell layer and in the inner shell layer (ISL) [28,30].…”
Section: Introductionmentioning
confidence: 99%